LA GESTIÓN COMUNICACIONAL DE LA GOBERNACIÓN DE CHIMBORAZO Y LA IDENTIDAD CORPORATIVA, EN LOS HABITANTES DE RIOBAMBA URBANO, JULIO-DICIEMBRE 2017 - Guevara López, Sofía Margarita (2019)
The governorate of Chimborazo province is the representation of the executive authority in the territory; it plays an important role in the development of the province through the articulation of its dependencies, carrying out actions and management that benefit the Chimborazo’s population. The governorate of Chimborazo works under three main axes: governability, citizen security and the political axis. To support this work was based on a bibliographical research that cites important authors of communication, on the other hand, two of the main theories of communication such as functionalism and structuralism, will lay the necessary foundations in this investigation, the same as Its objective is to analyze the communication management of the governorate of Chimborazo in the corporate identity, in the population of urban Riobamba. The methods that were used were the scientific method, inductive method, deductive method and the descriptive method, all of them helped to make the research viable and applied in a more practical way. The research was documentary-bibliographic, field research and descriptive research; the same ones that were complemented with interview techniques (question-answer) and with surveys made to the population, which was previously stratified. Thanks to this articulated work, it was possible to determine that the communication management of the government is outstanding and it is reflected in its identity and corporate image, which constitutes it as a solid institution before the Chimborazo’s population that is the main target public of the same.